The Role of the Regional Revenue Service in the Implementation of Self-Assessment System in Shopping Centers in Baguala District, Ambon City - Sri Sukmawati; Louisa M. Metekohy; Jumiati Tuharea (QISTINA: Jurnal Multidisiplin Indonesia, 2022)
This research seeks to reveal and clarify the role of the regional revenue agency in the application of a self-assessment system in shopping centers in Baguala district, Ambon City. Using a qualitative approach. The subjects of his research in this study were 3 employees of the Regional Revenue Service, 2 Business Actors (Indomaret, Ambon City Center) and the Head of the Regional Revenue Service as informants. The technique used is Purposive Sampling, where data sampling with certain considerations. The results showed that the role of the regional revenue service is very important because they can directly supervise what has been assigned directly by the State to them. Indirectly, they can also get a modern system that can bring stability to all the people in Ambon Maluku